(untitled) (World Economics and Finance Bulletin, 2022)
The Six Sigma strategy is one of the modern tools of managerial accounting, through which quality is measured in relation to the employee’s environmental status at work and the quality of service delivery efficiency for the customer. Most government service institutions use the old traditional form of management accounting, traditional forms do not serve the employee’s situation and greatly affects the provision of service to the customer, leading most institutes into being incapable of performing their service functions, in terms of providing service, sustainability, and quality improvement. The local beneficiaries are constantly expressing their dissatisfaction with the poor services and the lack of progress and performance in the institution. Therefore, the researchers in this research studied the extent to which using moderns management system (the Six Sigma strategy) can be applied to the health sector institutions in Baghdad and what are the obstacles that limit the interest from two perspectives, both Medical personnel and Medical patients had responded to the questioner to achieve a high degree of quality in the performance of the institution and more generalized results. The researchers concluded various results the most important of which is that using six sigma strategy can be achieved in the health sector institutes